2017
DOI: 10.1094/mpmi-07-17-0179-r
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Different Plant Cell Wall–Degrading Enzymes Is Important for Virulence of Fusarium graminearum

Abstract: Endo-polygalacturonases (PGs) and xylanases have been shown to play an important role during pathogenesis of some fungal pathogens of dicot plants, while their role in monocot pathogens is less defined. Pg1 and xyr1 genes of the wheat pathogen Fusarium graminearum encode the main PG and the major regulator of xylanase production, respectively. Single- and double-disrupted mutants for these genes were obtained to assess their contribution to fungal infection. Compared with wild-type strain, the ∆pg mutant showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…These results suggested that the STK-12-IGO-1 pathway is highly conserved between yeast and filamentous fungi. Like cellulolytic fungi, plant/insect pathogenic fungi also secrete hydrolytic enzymes that degrade components of the host epidermis during the infection process [59]. Thus, further analyses of the functions of STK-12 orthologs in plant/insect pathogenic fungi may aid in the development of novel anti-fungal strategies and more potent strains for insect biocontrol.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the STK-12-IGO-1 pathway is highly conserved between yeast and filamentous fungi. Like cellulolytic fungi, plant/insect pathogenic fungi also secrete hydrolytic enzymes that degrade components of the host epidermis during the infection process [59]. Thus, further analyses of the functions of STK-12 orthologs in plant/insect pathogenic fungi may aid in the development of novel anti-fungal strategies and more potent strains for insect biocontrol.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat plants ( Triticum aestivum cv. Nandu and Amaretto) were grown as reported in Paccanaro et al (2017). Inoculation experiments were performed on wheat spikes at anthesis according to Woriedh et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Heterotrophic fungi, for example, usually gain nutrients by secreting extracellular hydrolase. The hydrolases secreted by pathogenic fungi can damage plant cell wall by breaking down polysaccharides, thereby facilitating infection [ 20 ]. Decreased carbohydrate metabolism reduces the production of acetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%